Measuring reproductive health: review of community-based approaches to assessing morbidity - Ritu Sadana (The World Health Organization, 2000)
This article begins by reviewing selected past approaches to estimating the prevalence of a range of morbidities through the use of household or community-based interview surveys in developed and developing countries. Subsequently, it reviews epidemiological studies that have used a range of methods to estimate the prevalence of reproductive morbidities. A detailed review of recent community or hospital based health interview validation studies that compare self-reported, clinical and laboratory measures is presented. Studies from Bangladesh, Bolivia, China, Egypt, India, Indonesia, Nigeria, Philippines and Turkey provide empirical evidence that self-reported morbidity and observed morbidity measure different phenomena and therefore different aspects of reproductive health and illness. Rather than estimating the prevalence of morbidity, interview-based surveys may provide useful information about the disability or burden associated with reproductive health and illness.